If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6 + 6(4x + -9) = -7(-7x + 2) + -1 Reorder the terms: -6 + 6(-9 + 4x) = -7(-7x + 2) + -1 -6 + (-9 * 6 + 4x * 6) = -7(-7x + 2) + -1 -6 + (-54 + 24x) = -7(-7x + 2) + -1 Combine like terms: -6 + -54 = -60 -60 + 24x = -7(-7x + 2) + -1 Reorder the terms: -60 + 24x = -7(2 + -7x) + -1 -60 + 24x = (2 * -7 + -7x * -7) + -1 -60 + 24x = (-14 + 49x) + -1 Reorder the terms: -60 + 24x = -14 + -1 + 49x Combine like terms: -14 + -1 = -15 -60 + 24x = -15 + 49x Solving -60 + 24x = -15 + 49x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-49x' to each side of the equation. -60 + 24x + -49x = -15 + 49x + -49x Combine like terms: 24x + -49x = -25x -60 + -25x = -15 + 49x + -49x Combine like terms: 49x + -49x = 0 -60 + -25x = -15 + 0 -60 + -25x = -15 Add '60' to each side of the equation. -60 + 60 + -25x = -15 + 60 Combine like terms: -60 + 60 = 0 0 + -25x = -15 + 60 -25x = -15 + 60 Combine like terms: -15 + 60 = 45 -25x = 45 Divide each side by '-25'. x = -1.8 Simplifying x = -1.8
| 5n+7=7(n+1)2n | | -3g=14 | | 55-5X=7X+19 | | 11x+6=7x+30 | | 1.4y+14=6y-2 | | 3X+9=65-4X | | 1x+6=7x+30 | | -35-2x=13-10x | | 7x-11=59 | | 3X-4=12X-112 | | -x+-58=-20 | | 7x-11=54 | | 5x^4=1080x | | 7x-3y=42 | | 2X+20=10X-68 | | 4x=8x-3 | | 6(b-2)=3(b+8.5) | | 5x^2+33x-56=0 | | 5x+84=11x+12 | | 10+3(2xz+3y)+2xz= | | 7X-19=65 | | -28=13 | | 12x-5=91 | | 2(x+3y)-3y= | | 6(2r+3)+8r= | | -0.58=-8 | | 3x-23=-16+2x | | 0.2x=4 | | y=-10x+18 | | -7n=-294 | | 8x-18=46 | | -56-9x=10x+20 |